Uma revisão da teoria e evidência sobre sobre autonomia dos bancos centrais: há ganhos de eficiência para a política monetária? - Machado, Gustavo de Carvalho (2023)
The autonomy of central banks is a matter of great relevance, both in theoretical and practical aspects of monetary policy. This study focuses on the analysis of theories addressing the autonomy of central banks and its implications for monetary policies, with an emphasis on price stability. The theory of central bank autonomy gained prominence in the 1990s as a means to reduce state intervention in the economy and seek greater price stability. However, subsequent studies, especially following the subprime crisis, revealed a more complex and heterogeneous picture, challenging the original assumptions. In this research, we will examine the topic of central bank autonomy, analyzing both theoretical and empirical works, both internationally and in the Brazilian context. We will explore the academic debate and how autonomy sought institutionalization in Brazil. The aim is to understand the intricate interactions between central bank autonomy and price stability in the economy.